1999
DOI: 10.1046/j.1365-2796.1999.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of folic acid and betaine on fasting and postmethionine‐loading plasma homocysteine and methionine levels in chronic haemodialysis patients

Abstract: In chronic haemodialysis patients, fasting as well as postmethionine-loading plasma tHcy levels depend on folate status and decrease after folic acid therapy. Increased postload homocysteine levels in these patients therefore do not necessarily indicate an impaired transsulphuration capacity only; alternatively, folate may indirectly influence transsulphuration. The elucidation of the complex pathogenesis of hyperhomocysteinaemia in chronic renal failure requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 25 publications
3
22
0
3
Order By: Relevance
“…Previous studies have shown that betaine is effective in suppressing methionine-induced hyperhomocysteinemia in humans 33,34) and rats. 35,36) In rats, Yagisawa et al 35,36) found that hyperhomocysteinemia induced by intravenous injection with methionine was suppressed by concurrent injection with betaine or dietary supplementation with betaine.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that betaine is effective in suppressing methionine-induced hyperhomocysteinemia in humans 33,34) and rats. 35,36) In rats, Yagisawa et al 35,36) found that hyperhomocysteinemia induced by intravenous injection with methionine was suppressed by concurrent injection with betaine or dietary supplementation with betaine.…”
Section: Discussionmentioning
confidence: 98%
“…The effects of L-methionine were observed at high micromolar and low millimolar concentrations of L-methionine, which are well within the range of plasma levels after methionine loading. 31 Higher concentrations between 5 and 20 mM L-methionine were required to confirm increased HO-1 activity in a cell-free assay of bilirubin. This inevitable loss of sensitivity during the "ex vivo" measurement of specific enzyme activity in a broken cell system has been reported previously and is a result of induced HO-1 not being fully recoverable during the complex preparation of lysate from intact cells that were preexposed to inducing agents.…”
Section: E198mentioning
confidence: 99%
“…Supplementation with betaine, starting at 3 g twice a day, is experimental and has yielded conflicting results, but can be used in very highrisk patients. 79,80 Once the patient is within goal range, a fasting tHcy can be repeated on a yearly basis. 9…”
Section: Suggestions For Current Homocysteine Screening and Managementmentioning
confidence: 99%